Effect of frailty on outcomes of endovascular treatment for acute ischaemic stroke in older patients. (29th April 2022) - Tan, Benjamin Y Q; Ho, Jamie S Y; Leow, Aloysius S; Chia, Magdalene L J; Sia, Ching Hui; Koh, Ying Ying; Seetharaman, Santhosh K; Yang, Cunli; Gopinathan, Anil; Teoh, Hock Luen; Sharma, Vijay K; Seet, Raymond C S; et al.
Abstract: Background: frailty has been shown to be a better predictor of clinical outcomes than age alone across many diseases. Few studies have examined the relationship between frailty, stroke and stroke interventions such as endovascular thrombectomy (EVT). Objective: we aimed to investigate the impact of frailty measured by clinical frailty scale (CFS) on clinical outcomes after EVT for acute ischemic stroke (AIS) in older patients ≥70 years. Methods: in this retrospective cohort study, we included all consecutive AIS patients age ≥ 70 years receiving EVT at a single comprehensive stroke centre. Patients with CFS of 1–3 were defined as not frail, and CFS > 3 was defined as frail. The primary outcome was modified Rankin Score (mRS) at 90 days. The secondary outcomes included duration of hospitalisation, in-hospital mortality, carer requirement, successful reperfusion, symptomatic intracranial haemorrhage and haemorrhagic transformation. Results: a total of 198 patients were included. The mean age was 78.1 years and 52.0% were female. Frail patients were older, more likely to be female, had more co-morbidities. CFS was significantly associated with poor functional outcome after adjustment for age, NIHSS and time to intervention (adjusted odds ratio [aOR] 1.54, 95% confidence interval [CI] 1.04–2.28, P  = 0.032). There was trend towards higher mortality rate in frail patients (frail: 18.3%; non-frail: 9.6%; P  = 0.080). There were no significant differences in other secondary outcomes except increased carer requirement post discharge in frail patients (frail: 91.6%; non-frail: 72.8%; P  = 0.002). Conclusions: frailty was associated with poorer functional outcome at 90 days post-EVT in patients ≥ 70 years.